2022
DOI: 10.1186/s12889-022-12694-z
|View full text |Cite
|
Sign up to set email alerts
|

Experience of clinical services shapes attitudes to mental health data sharing: findings from a UK-wide survey

Abstract: Background Routinely-collected mental health data could deliver novel insights for mental health research. However, patients’ willingness to share their mental health data remains largely unknown. We investigated factors influencing likelihood of sharing these data for research purposes amongst people with and without experience of mental illness. Methods We collected responses from a diverse sample of UK National Health Service (NHS) users (n = 21… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…It is important to note that these comments were made in 2019, prior to the onset of the Covid-19 pandemic. This highlights that whilst the pandemic has increased the burden on mental health services (Lavis, 2022), these services were already struggling to meet people’s needs prior to the pandemic (Kirkham et al, 2022). Interestingly, previous research has shown that positive experiences of mental health services are associated with more positive attitudes to mental health data sharing (Kirkham et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is important to note that these comments were made in 2019, prior to the onset of the Covid-19 pandemic. This highlights that whilst the pandemic has increased the burden on mental health services (Lavis, 2022), these services were already struggling to meet people’s needs prior to the pandemic (Kirkham et al, 2022). Interestingly, previous research has shown that positive experiences of mental health services are associated with more positive attitudes to mental health data sharing (Kirkham et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Individuals who took part in a previous survey by our research team (which also focused on the topic of sharing mental health data; Kirkham et al, 2022) were asked to leave their email address if they wanted to take part in an interview. This list of email addresses was used to invite people to take part in the present interview study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations